Transportation price benchmarking: implications for firm performance. Issue 4 (3rd May 2016) - Swanson, David
Abstract : Purpose: – The purpose of this paper is to understand how transportation price benchmarking impacts firm performance. Design/methodology/approach: – In this study, firm transportation costs and other financial variables are examined with regression analysis. This study extends empirical research on benchmarking by using current data, taking a longitudinal approach, using additional research methods, and by taking a contingency theory approach to examine firm performance contingent on the relative size of benchmarking information. Findings: – Firms can reduce prices paid for transportation (thereby improving firm performance) by participating in benchmarking consortiums, and the amount of price reduction is contingent on the size of firm transportation spending relative to that of the benchmarked firms. Furthermore, the contingent relationship is concave, which indicates that participation in benchmarking consortiums can be optimized. Research limitations/implications: – Despite the wide range of companies in this sample and the longitudinal approach of this research, this study examined benchmarking performance in just one marketplace (truckload transportation). Practical implications: – The findings help managers to lower transportation costs and optimize the benefits that can be obtained from benchmarking. Originality/value: – Transportation prices paid by firms are difficult to obtain because firms are not required to isolate and disclose this information on financial statements. Therefore, the transparency of transportation pricing data in this study which include a wide cross-section of firms provides a unique examination of actual transportation prices and how they can be used for benchmarking.